2019
DOI: 10.1073/pnas.1818859116
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in consumption of goods and services adds to racial–ethnic disparities in air pollution exposure

Abstract: Fine particulate matter (PM2.5) air pollution exposure is the largest environmental health risk factor in the United States. Here, we link PM2.5exposure to the human activities responsible for PM2.5pollution. We use these results to explore “pollution inequity”: the difference between the environmental health damage caused by a racial–ethnic group and the damage that group experiences. We show that, in the United States, PM2.5exposure is disproportionately caused by consumption of goods and services mainly by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
409
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(431 citation statements)
references
References 25 publications
16
409
1
5
Order By: Relevance
“…Air pollutant emissions in 2030 are estimated by scaling 2014 emissions from the US National Emissions Inventory (NEI) (EPA 2017) based on regionspecific changes in economic variables in the period from 2014 to 2030 estimated by USREP, following the approach of Thompson et al (2014). First, 2014 emissions are aggregated across pollutant species, time, and space to match the specifications of InMAP (Tessum et al 2019). Next, we match the EPA Source Classification Codes used to categorize individual emission sources to relevant economic variables estimated by USREP.…”
Section: Methodsmentioning
confidence: 99%
“…Air pollutant emissions in 2030 are estimated by scaling 2014 emissions from the US National Emissions Inventory (NEI) (EPA 2017) based on regionspecific changes in economic variables in the period from 2014 to 2030 estimated by USREP, following the approach of Thompson et al (2014). First, 2014 emissions are aggregated across pollutant species, time, and space to match the specifications of InMAP (Tessum et al 2019). Next, we match the EPA Source Classification Codes used to categorize individual emission sources to relevant economic variables estimated by USREP.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, Collins et al (2016) colocate facilities that are outliers in toxic releases and low income communities of color, linking disproportionality in the production of toxic emissions to disproportional exposure. Focusing on air pollution, Tessum et al (2019) build an economy-wide model, linking emission sources, end uses and end users associated with fine particulate matter (PM 2.5 ) and highlight disproportionality in the racial-ethnic composition of groups producing PM 2.5 pollution versus those subjected to exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than designing regulations targeted at all facilities, a disproportionality approach suggests identifying and targeting egregious polluters. This approach has proved fruitful in attribution research in the climate policy community (Frumhoff et al 2015, Ekwurzel et al 2017 and in efforts to mitigate environmental injustice due to the co-location of egregious polluters and low income communities of color (Grant et al 2010, Collins et al 2016, Tessum et al 2019. Moreover, solutions that aim to reconfigure production at egregiously polluting facilities to meet industry averages, rather than closing such facilities, may generate less political opposition to regulation (Berry 2008, Collins 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have documented and quantified racial/ ethnic inequity in the level of exposure to fine PM and consumption of goods and services in the United States (Tessum et al 2019). Several studies in other countries such as China have shown that people with lower socio-economic status (SES) are at higher risk of exposure to air pollution (Li et al 2018, Ma et al 2019.…”
Section: Introductionmentioning
confidence: 99%